Pengaruh Green Marketing Dan Brand Image Terhadap Minat Beli Konsumen - Purnomo, Nanto; Azizah, Luluk Nur (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
The purpose of green marketing is not solely to make a profit, but rather the company aims to raise awareness of environmental issues. AQUA's green marketing is carried out through the AQUA campaign, focusing on health, specifically "It All Starts With Us," as part of the AQUA Initiative for a Healthy Indonesia while also preserving the environment by reducing plastic waste. Not only the campaign but AQUA also brands itself to demonstrate its commitment to maintaining the quality of its products for health and preserving the environment. This study aims to determine whether green marketing and brand image influence consumer purchasing interest in the study of AQUA products. This research utilizes SmartPLS 3.0 analysis software, and the results indicate that green marketing has a positive and significant impact on consumer buying interest. Additionally, the brand image built by AQUA has a positive and significant effect on AQUA consumers' buying interest.Keywords: Green Marketing; Brand Image; Consumer Buying Interest.